(untitled) (مجلة دراسات إقلیمیة, 2026)
Research Idea: Foreign direct investment (FDI) is defined as the investment of foreign funds in fixed capital assets in a particular country, the research problem is the nature of the agricultural sector in a sample of developing countries, including Iraq, Egypt, Turkey, and Thailand, which was characterized by its inability to produce to the extent that it is allowed to export to foreign markets. Objective: The research aims to study the role of foreign direct investment companies in increasing agricultural production and exports during the period 1990-2023, based on the hypothesis that the mentioned investment companies contribute positively to increasing agricultural exports. Hypothesis: In order to prove the research hypothesis, time series data, the usual least squares method, the ARDL methodology, and the E_Views_12 program were used to estimate and analyze the impact of foreign direct investment and a number of variables including the foreign exchange rate, inflation rate, agricultural output values, agricultural government support in agricultural exports and in the short and long term, as well as using the ECM model to correct the error to ensure that there is a relationship between the independent variables and the dependent variable. Methodology: The research relied on the method of linking two directions, a descriptive approach based on the theoretical studies that studied this topic, and a quantitative approach that depends on the methods and methods of econometrics and then interpreting the results of the quantitative method to evaluate the applied aspect. Results: We conclude from the above the contribution of foreign investment companies to the economic and agricultural transformation and the weakness of the infrastructure of the research sample countries to the extent that they are not suitable for attracting foreign companies optimally, and the absence of the leading role of agricultural extension agencies in the field of using modern technologies. Conclusion: We recommend rehabilitating the reality of agriculture in the sample countries, adopting programs for the rehabilitation and training of agricultural workers, and working to achieve the greatest possible political and social stability.